TINJAUAN MUSIKOLOGIS DIKIE RABANO DALAM RITUAL BAOK ANAK KA AIE DI NAGARI BAWAN KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Yeni, Yudi Asrul; Asril, Asril; Kamal, Zahara (Grenek: Jurnal Seni Musik, 2020)
The study aims to discuss dikie rabano™s function in the context of the baok anak ka aie (shower down) ritual and to discuss the form of the presentasion of dikie rabano in the care-bathing ritual at Nagari Bawan. The research methods use are qualitative methods with data collection techniques: observastion, interviews, and documentation. As a result of the study, dikie rabano™s function was that of both customary and religious education and of promoting a grammatical relationship between the family and surrounding communities. In terms of the presentation, there is an art in dikie rabano that begins with vowels or song solo and instructed by the vocal group together while playing rabano™s instrument rhythm pattern, whereas in terms of its musical shape, it can be seen as a continuous rhythm pattern.